(untitled) - Gevorkian, Peter (New York, NY., 2007)
Sustainable Energy Systems Engineering delivers the insight you need to produce wiring plans, calculations, and systems integration. Plus, it also features: Charts, tables, and diagrams that clearly illustrate each concept. Coverage of NEC Section 690: the basis of all solar power systems design. A useful selection of California Energy Commission rebate plan applications. Systems component selection and integration. Technical and financial feasibility studies. Power demand and voltage drop calculations. Short circuit analysis. Service grid connectivity coordination. And more!
Keywords: Renewable energy sources,Sustainable buildings